Construction of OCCM for realization of permutations of definite properties with theoretically infinite length - Ianovska, Olena (Видавництво Львівської політехніки, 2010)
This paper deals with algorithm for construction of simple one-dimension cascades of constructive modules (OCCM) for realization of complete permutations with arbitrary length and definite properties.
Keywords: complete permutations; one-dimension cascade of constructive modules; primary and side functions